Late Syn-Rift Turbidite Systems in the North Sumatra Basin - Lawrence D. Meckel, III (Ikatan Ahli Geologi Indonesia, 2013)
The North Sumatra Basin in Indonesia is one of the most prolific petroleum provinces in SE Asia. It has been affected by rifting, transtensional and transpressional shear, and compression from the Paleogene to present day. This complex tectonic history has created numerous opportunities for petroleum exploration, including an inverted deepwater turbidite play that has been relatively under-explored to date.